SnAvi – a new tandem tag for high-affinity protein-complex purification - Schäffer, Ursula (Oxford University Press, 2010)
Systematic tandem-affinity-purification (TAP) of protein complexes was tremendously successful in yeast and has changed the general concept of how we understand protein function in eukaryotic cells. The transfer of this method to other model organisms has been difficult and may require specific adaptations. We were especially interested to establish a cell-type-specific TAP system for Caenorhabditis elegans, a model animal well suited to high-throughput analysis, proteomics and systems biology. By combining the high-affinity interaction between in vivo biotinylated target-proteins and streptavidin with the usage of a newly identified epitope of the publicly shared SB1 monoclonal antibody we created a novel in vivo fluorescent tag, the SnAvi-Tag. We show the versatile application of the SnAvi-Tag in Escherichia coli, vertebrate cells and in C. elegans for tandem affinity purification of protein complexes, western blotting and also for the in vivo sub-cellular localization of labelled proteins.